STRATEGI OPTIMASI TEKNOLOGI INFORMASI DAN KOMUNIKASI DALAM MENDUKUNG PROSES DIGITALISASI DI BALAI DESA JABUNG SISIR - Karim, Abdul; Rohman, Moh. Kamalul; Ali, Moh. Haidar; Maulana, Huda Maksum; Ramadan, M. Rizki (Fakultas Sains dan Teknologi, Universitas Ibrahimy, 2025)
Technology has an important role so that digital public services can run as they should. Regarding administration and information in Jabungsisir village, it is still inadequate, as shown by several facts in the field, including (1) the computer equipment in the Jabungsisir village hall still uses old CPUs and Windows XP. and the official Jabungsisir village website does not yet exist, information regarding Jabungsisir village is still integrated with the Probobolinggo district government website. (2) the use of information and communication technology (ICT) is not optimal, for example virtual meetings using Zoom or Google Meet, even though this is very important when face-to-face meetings are not possible, for example during an outbreak such as Covid-19 last year. . (3) Likewise, the storage of village documents has not been carried out in the cloud/virtual way, so data is vulnerable to loss when damage occurs to the data processing equipment. The method used in this research is a descriptive qualitative method to obtain in-depth information about how Information and Communication Technology Optimization Strategies support the Data Digitalization Process at the Jabungsisir Village Office, Paiton District, Probolinggo Regency. The results of this research are the creation of a Jabungsisir village website, virtual data storage and an understanding of the use of ICT for long distance meetings.